New angiogenic regulators produced by TAMs: Perspective for targeting tumor angiogenesis - Larionova, Irina V.; Kazakova, Elena; Gerashchenko, Tatiana; Kzhyshkowska, Julia (Cancers, 2021)
Angiogenesis is crucial to the supply of a growing tumor with nutrition and oxygen. Inhibition of angiogenesis is one of the main treatment strategies for colorectal, lung, breast, renal, and other solid cancers. However, currently applied drugs that target VEGF or receptor tyrosine kinases have limited efficiency, which raises a question concerning the mechanism of patient resistance to the already developed drugs. Tumor-associated macrophages (TAMs) were identified in the animal tumor models as a key inducer of the angiogenic switch. TAMs represent a potent source not only for VEGF, but also for a number of other pro-angiogenic factors. Our review provides information about the activity of secreted regulators of angiogenesis produced by TAMs. They include members of SEMA and S100A families, chitinase-like proteins, osteopontin, and SPARC. The COX-2, Tie2, and other factors that control the pro-angiogenic activity of TAMs are also discussed. We highlight how these recent findings explain the limitations in the efficiency of current anti-angiogenic therapy. Additionally, we describe genetic and posttranscriptional mechanisms that control the expression of factors regulating angiogenesis. Finally, we present prospects for the complex targeting of the pro-angiogenic activity of TAMs.
Published: 29 June 2021
Gesehen am 21.06.2022